CORPORATE SOCIAL RESPONSIBILITY IN GHANA: A COMPARATIVE ANALYSIS AND BUSINESS IMPERATIVE - Martin Owusu Ansah (International Review of Management and Marketing, 2013)
The grounds underpinning companies resorting to different Corporate Social Responsibility (CSR) practices are not obvious. Rationally, the profit making motive is at the front position of the companies’ goals as well as other factors which are hidden. This has led to a keen interest in promoting CSR among companies in Ghana than it was before. Through observations, document analysis and conduction of interviews of managers among the selected organizations, this paper sought to examine the CSR policies of five companies in Ghana and the associated benefits enjoyed by Ghanaians. Specifically, the paper aimed at determining the nature and impact – present and potential - of the selected companies’ CSR policies in Ghana and examined the assumptions behind the practice of CSR among the chosen companies. The methods used comprised primary data and secondary data sources. Convenient sampling technique was used for the study. The data were collected, collated and analyzed using charts and diagrams for easy interpretation. It was revealed from the research that, CSR programmes were community-focus initiatives, programmes on education as well as programmes in developing communities. It was therefore concluded that, there should be a law on CSR in Ghana and a course on CSR to train experts in that area.